The Role of Basic Education in the Attainment of Vision 20: 2020 - Lawal, A. A; Ojo, O. J.; Murtala, A. T. (International Journal of Educational Management, 2022)
Education is said to be an indispensable instrument for not only economic and political advancement but also for progress in all human endeavours. This paper examines the role of basic education in the attainment of vision 20:2020. The concepts and objectives of Basic Education are looked into. The concept of vision 20:2020 and its antecedents are discussed while the bottlenecks to the attainment of vision 20:2020 which include corruption, politicking within education system, Niger Delta crisis, and inconsistency in government policies. How Basic Education could help in the attainment of vision 20:2020 was also discussed, and finally, recommendation was made which include: adequate funding of Basic Education, strategizing measures towards attaining the vision 20:2020.